2004
DOI: 10.1093/jn/134.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Isomers of Conjugated Linoleic Acid Differ in Their Effects on Angiogenesis and Survival of Mouse Mammary Adipose Vasculature

Abstract: Dietary conjugated linoleic acid (CLA) is a cancer chemopreventive agent that has been shown to inhibit angiogenesis in vivo and in vitro, and to decrease vascular endothelial growth factor (VEGF) and Flk-1 concentrations in the mouse mammary gland. To determine which isomer mediates the antiangiogenic effects of CLA in vivo, the effects of diets supplemented with 5 or 10 g/kg c9,t11- or t10,c12-CLA isomers were compared in CD2F1Cr mice. Both isomers inhibited functional vascularization of a matrigel pellet in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 57 publications
0
48
1
4
Order By: Relevance
“…It and the predominant natural isomer c9,t11-CLA, have been studied most extensively since they are each available commercially at relatively high purity. Although both CLA isomers were found to be equally efficacious in inhibiting rat mammary carcinogenesis [31] and angiogenesis [32], t10,c12-CLA is the more potent isomer in most in vitro studies. In TM4t mammary tumor cells, for example, we found that t10,c12-CLA is approximately five times more potent than c9,t11-CLA in decreasing viable cell number.…”
Section: Discussionmentioning
confidence: 95%
“…It and the predominant natural isomer c9,t11-CLA, have been studied most extensively since they are each available commercially at relatively high purity. Although both CLA isomers were found to be equally efficacious in inhibiting rat mammary carcinogenesis [31] and angiogenesis [32], t10,c12-CLA is the more potent isomer in most in vitro studies. In TM4t mammary tumor cells, for example, we found that t10,c12-CLA is approximately five times more potent than c9,t11-CLA in decreasing viable cell number.…”
Section: Discussionmentioning
confidence: 95%
“…This anti-angiogenic effect is likely to have been related to tumor suppression by CDHA, 18) and may also have been related to the anti-obesity effect of CDHA, 15) since angiogenesis has been associated with an increase in white adipose tissue. 40) The DAS assay showed that neovascularization of the mouse subcutaneous tissues, which was triggered by DLD-1 cells, was effectively inhibited by the oral administration of CDHA (Fig. 6).…”
Section: Control (X200)mentioning
confidence: 97%
“…DHA, CLA, -T3 and thalidomide were used as positive controls of this effect. 33,[36][37][38][39][40] Thalidomide is used as a therapeutic agent for angiogenesis disease.…”
Section: Cells and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Les effets biologiques attribués aux CLA sont nombreux, souvent mal compris, voire contradictoires. Les CLA sont décrits comme des modulateurs de la réponse immunitaire [1,2], comme possédant des propriétés anticancé-reuses [3,4], anti-athérogéniques [5,6], antidiabétiques [7,8] ou encore comme responsables d'une augmentation de la résistance à l'insuline [9,10]. L'effet réducteur des CLA sur la masse grasse décrit dans plusieurs modèles animaux [11][12][13][14] apparaît très spectaculaire, même si les études menées chez l'Homme ne sont pas aussi démonstratrices [15,16].…”
unclassified